2011
DOI: 10.1007/s13351-011-0507-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of the air-sea interaction during Typhoon Kaemi (2006)

Abstract: The high-resolution Weather Research and Forecasting (WRF) model is coupled to the Princeton Ocean Model (POM) to investigate the effect of air-sea interaction during Typhoon Kaemi that formed in the Northwest Pacific at 0000 UTC 19 July 2006. The coupled model can reasonably reproduce the major features of ocean response to the moving tropical cyclone (TC) forcing, including the deepening of ocean mixed layer (ML), cooling of sea surface temperature (SST), and decaying of typhoon.Due to the appearance of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Due to higher rainfall in the left side of the typhoon track, lower SST prevailed. Liu et al (2011) identified lower temperatures over typhoon track during 22-23 July and found there are higher temperatures and rainfall over southern part of typhoon track. Higher SST can be observed over southern side of study area, especially over west coast of Philippines, during the typhoon.…”
Section: Cumulative Rainfall Variations During Typhoon Kaemimentioning
confidence: 94%
See 1 more Smart Citation
“…Due to higher rainfall in the left side of the typhoon track, lower SST prevailed. Liu et al (2011) identified lower temperatures over typhoon track during 22-23 July and found there are higher temperatures and rainfall over southern part of typhoon track. Higher SST can be observed over southern side of study area, especially over west coast of Philippines, during the typhoon.…”
Section: Cumulative Rainfall Variations During Typhoon Kaemimentioning
confidence: 94%
“…However, there is a small patch of 2°C higher SST over the east Philippines. Liu et al (2011) studied about the Typhoon Kaemi and determined the SST cooling at selected points at left and right side of the typhoon track. The cyclonic rotation induced by Ekman pumping caused entrainment and upwelling (Tsai et al 2008) and drop in temperature, which illustrates the boundary current system and regional geometry and bathymetry interaction with the typhoon-induced circulation.…”
Section: General Description Of Typhoon Kaemimentioning
confidence: 99%
“…Although the extreme rainstorm occurred in Henan after July 18, 2021, the rainfall had appeared to the east of Henan before July 18, 2021 (Figure S2a-d). Such a westward movement and enhancement of rainfall after July 18, 2021 may be associated with typhoon activities, which could transport excessive water vapor from the southeastern coast of China to inland regions, bringing heavy rainfall to central-northern China (Li et al, 2006). On one hand, the typhoon leads to the rainstorm directly when it moves northward to the middle and high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the typhoon leads to the rainstorm directly when it moves northward to the middle and high latitudes. On the other hand, the southeasterly airflow between the typhoon and WPSH transports the warm and moist air from the sea to central-northern China, providing abundant water vapor for the inland rainfall (Klein et al, 2002;Li et al, 2006). Among them, the dynamic effects of typhoon play a dominant role to the rainstorm event, with secondary contribution from thermodynamic effects via moisture conditions (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…5d). As wind suction and carrying volume eff ect caused by upwelling of deep cold water decreased the SST and SAL had a small increase on July 25, 2014 (Liu et al, 2011). There was a 1-4-mm/h rainfall in average between July 26 to 28 (data from http://www.remss.…”
Section: Infl Uence Of T-cs On the Y-bmentioning
confidence: 99%